PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS WORDWALL PADA MATERI PELAJARAN IPA KELAS IV DI SDN BANJARSARI 01 - Septiani, Piya; Hayu, Wiworo Retnadi Rias; Rajagukguk, Zahrah Fitrah (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
Measuring student success in their learning activities requires a success measurement tool which we usually call learning evaluation. The use of learning assessments will also serve as a reference point in the future for educators, allowing them to further improve the learning processes that have been carried out. Thus, the aim of this research is to determine the stages of development and feasibility of learning-based evaluation wordwall on class IV science lesson material at SDN Banjarsari 01. This type of research RD using a development model ADDIE. ADDIE is an extension of Analysis, Design, Development, Implementation, dan Evaluation. The research was conducted at SDN Banjarsari 01 in class IV in the 2023/2024 academic year. The research subjects in this study were fourth grade students. Tests, questionnaires, validation sheets are data collection techniques used in research. The results of the feasibility test from expert validators, namely material validators obtained a percentage of 89.3%, and media validators obtained a percentage of 87.7% entering the very valid category. The assessment results from the teacher response questionnaire obtained a percentage of 98%, while the assessment of responses from students had a percentage score of 65.42%. Therefore, it can be concluded that the wordwall-based learning evaluation development product is suitable for use in learning evaluation activities in class IV at SDN Banjarsari 01.